The Sound Bubble: A context-sensitive space in the space. Issue 1 (7th March 2017) - Eriksson, Martin Ljungdahl; Atienza, Ricardo; Pareto, Lena
Abstract : The design of sonic environments is in need of more active strategies, taking into account not only the physical but also the social and sensorial aspects of a place. This implies abandoning traditional, mono-disciplinary responses in favour of interdisciplinary methods and approaches. In this study we explored the possibility of inserting context-sensitive sound textures to improve the experience of an activity-based office workplace. For this purpose, we developed the concept of the 'sound bubble' – a micro-space in which the user is embedded by a semi-transparent added sound environment that will operate as a subtle sound mask, attracting the attention without needing to hide the disturbing environment. This should help users (the workers) to stay in an 'everyday listening' mode. This means, not focusing on the environment in particular but on their tasks, while preserving the link with the surrounding space and activities.